From 56f0845819e238ed3ca9efac41d7d875b3119388 Mon Sep 17 00:00:00 2001 From: Ryan Chung <87027981+ryangchung@users.noreply.github.com> Date: Tue, 24 Dec 2024 18:10:35 +0000 Subject: [PATCH] fix: lint in main --- .../questions/comp2804/2014-fall-midterm/7/solution.md | 2 +- src/content/questions/comp2804/2015-fall-final/4/solution.md | 2 +- .../questions/comp2804/2015-winter-final/4/solution.md | 4 ++-- .../questions/comp2804/2016-fall-midterm/9/solution.md | 4 ++-- .../questions/comp2804/2017-fall-midterm/9/solution.md | 2 +- src/content/questions/comp2804/2018-fall-final/6/solution.md | 2 +- .../questions/comp2804/2022-winter-final/6/solution.md | 2 +- 7 files changed, 9 insertions(+), 9 deletions(-) diff --git a/src/content/questions/comp2804/2014-fall-midterm/7/solution.md b/src/content/questions/comp2804/2014-fall-midterm/7/solution.md index 31fcbe69..c0c3253d 100644 --- a/src/content/questions/comp2804/2014-fall-midterm/7/solution.md +++ b/src/content/questions/comp2804/2014-fall-midterm/7/solution.md @@ -1,6 +1,6 @@ ${(5x-36)}^{100}$ -$ = \sum^{100}_{k=0} \binom{100}{k} {(5x)}^{n-k} {(-3y)}^{k} $ +$ = \sum^{100}\_{k=0} \binom{100}{k} {(5x)}^{n-k} {(-3y)}^{k} $ We only consider $k=80$, as it results in $y^{80}$. diff --git a/src/content/questions/comp2804/2015-fall-final/4/solution.md b/src/content/questions/comp2804/2015-fall-final/4/solution.md index fb663a23..f8f4d891 100644 --- a/src/content/questions/comp2804/2015-fall-final/4/solution.md +++ b/src/content/questions/comp2804/2015-fall-final/4/solution.md @@ -1,4 +1,4 @@ -$ = \sum^{20}_{k=0} \binom{20}{k} {(-3x)}^{n-k} {(5y)}^{k} $ +$ = \sum^{20}\_{k=0} \binom{20}{k} {(-3x)}^{n-k} {(5y)}^{k} $ We only consider $k=5$, as it results in $y^{5}$. diff --git a/src/content/questions/comp2804/2015-winter-final/4/solution.md b/src/content/questions/comp2804/2015-winter-final/4/solution.md index 34455183..62d4d783 100644 --- a/src/content/questions/comp2804/2015-winter-final/4/solution.md +++ b/src/content/questions/comp2804/2015-winter-final/4/solution.md @@ -1,6 +1,6 @@ $ {(2x-7y)}^{15} $ -$ = \sum_{k=0}^{15} \binom{15}{k} {(2x)}^{n-k} {(-7y)}^{k} $ +$ = \sum\_{k=0}^{15} \binom{15}{k} {(2x)}^{n-k} {(-7y)}^{k} $ We only consider $k=11$, as it results in $y^{11}$. @@ -10,4 +10,4 @@ $ = \binom{15}{11} \cdot 2^{4} \cdot {(-7)}^{11} \cdot x^4 \cdot y^{11} $ $ = - \binom{15}{4} \cdot 2^{4} \cdot 7^{11} \cdot x^4 \cdot y^{11} $ -Thus, the coefficient of $ x^{4}y^{11} $ in the expansion of $ {(2x-7y)}^{15} $ is $ - \binom{15}{11} \cdot {2}^{4} \cdot {7}^{11} $ \ No newline at end of file +Thus, the coefficient of $ x^{4}y^{11} $ in the expansion of $ {(2x-7y)}^{15} $ is $ - \binom{15}{11} \cdot {2}^{4} \cdot {7}^{11} $ diff --git a/src/content/questions/comp2804/2016-fall-midterm/9/solution.md b/src/content/questions/comp2804/2016-fall-midterm/9/solution.md index 80b2dcce..0fbcc920 100644 --- a/src/content/questions/comp2804/2016-fall-midterm/9/solution.md +++ b/src/content/questions/comp2804/2016-fall-midterm/9/solution.md @@ -1,4 +1,4 @@ -$ = \sum^{50}_{k=0} \binom{50}{k} {(5x)}^{n-k} {(-7y)}^k $ +$ = \sum^{50}\_{k=0} \binom{50}{k} {(5x)}^{n-k} {(-7y)}^k $ We only consider $k=26$, as it results in $y^{26}$. @@ -8,4 +8,4 @@ $ = \binom{50}{26} \cdot {(5)}^{24} \cdot x^{24} \cdot {(-7)}^{26} \cdot y^{26} $ = \binom{50}{26} \cdot 5^{24} \cdot 7^{26} \cdot x^{24} \cdot y^{26} $ -Thus, the coefficient is $ \binom{50}{26} \cdot 5^{24} \cdot 7^{26} $ \ No newline at end of file +Thus, the coefficient is $ \binom{50}{26} \cdot 5^{24} \cdot 7^{26} $ diff --git a/src/content/questions/comp2804/2017-fall-midterm/9/solution.md b/src/content/questions/comp2804/2017-fall-midterm/9/solution.md index cc40c4a9..0ff3c1bd 100644 --- a/src/content/questions/comp2804/2017-fall-midterm/9/solution.md +++ b/src/content/questions/comp2804/2017-fall-midterm/9/solution.md @@ -1,4 +1,4 @@ -$ = \sum^{100}_{k=0} \binom{100}{k} {(7x)}^{n-k} {(-13y)}^{k} $ +$ = \sum^{100}\_{k=0} \binom{100}{k} {(7x)}^{n-k} {(-13y)}^{k} $ We only consider $k=80$, as it results in $y^{80}$. diff --git a/src/content/questions/comp2804/2018-fall-final/6/solution.md b/src/content/questions/comp2804/2018-fall-final/6/solution.md index cbf2a2b5..5f2a4160 100644 --- a/src/content/questions/comp2804/2018-fall-final/6/solution.md +++ b/src/content/questions/comp2804/2018-fall-final/6/solution.md @@ -1,4 +1,4 @@ -$ = \sum_{k=0}^{55} \binom{55}{k} {(5x)}^{n-k} {(-3y)}^{k} $ +$ = \sum\_{k=0}^{55} \binom{55}{k} {(5x)}^{n-k} {(-3y)}^{k} $ We only consider $k=35$, as it results in $y^{35}$. diff --git a/src/content/questions/comp2804/2022-winter-final/6/solution.md b/src/content/questions/comp2804/2022-winter-final/6/solution.md index 713b22cd..a52bd120 100644 --- a/src/content/questions/comp2804/2022-winter-final/6/solution.md +++ b/src/content/questions/comp2804/2022-winter-final/6/solution.md @@ -1,6 +1,6 @@ $ (2x - 3y)^{30} $ -$ = \sum_{k=0}^{30} \binom{30}{k} \cdot (2x)^{n-k} \cdot (-3y)^{k} $ +$ = \sum\_{k=0}^{30} \binom{30}{k} \cdot (2x)^{n-k} \cdot (-3y)^{k} $ We only consider $k=20$, as it results in $y^{20}$.